Effect of Water Quality on Pentlandite-Pyroxene Floatability with an Emphasis on Calcium Ions (ABSTRACT PAGE) (International Mineral Processing Congress, 2003)
"The Merensky Reef is a platinum group minerals (PGM) bearing reef in the Bushveld Igneous Complex in South Africa. The reef has been treated by bulk PGM and sulphide flotation with the aim of maximisingthe valuable minerals recovery and gangue minerals rejection.Synthetic water with a calcium concentration of 80 ppm and 500 ppm was prepared and the flotation results obtained were compared to a simple electrolyte in order to determine the effect water quality has on pentlandite and pyroxene surface alteration and, ultimately, floatability. During the study, the possible effect of interactions between the minerals investigated and Ca2+ ions in the presence of sodium isobutyl xanthate was studied at pH 6 and pH 9 by means of zeta potential determinations, microflotation tests and ToF-SIMS analysis.The results obtained on 1:1 pentlandite-pyroxene mixtures showed that the quality of process water plays an important role in flotation. The flotation recoveries of pentlandite and pyroxene were lower in synthetic process water compared to those obtained in a simple electrolyte solution."